VEGF directly suppresses activation of T cells from ascites secondary to ovarian cancer via VEGF receptor type 2 - Gavalas, N.G.; Tsiatas, M.; Tsitsilonis, O.; Politi, E.; Ioannou, K.; Ziogas, A.C.; Rodolakis, A.; Vlahos, G.; Thomakos, N.; Haidopoulos, D.; Terpos, E.; Antsaklis, A.; et al. (British Journal of Cancer, 2012)
Background:Vascular endothelial growth factor action in tumour angiogenesis is well characterised; nevertheless, it functions as a key element in the promotion of the immune systems evasion by tumours. We sought to investigate the possible direct effect of VEGF on T-cell activation and through which type of VEGF receptor it exerts this effect on cells isolated from ovarian cancer patients ascites.Methods:T cells isolated from the ascites of ovarian cancer patients were cultured with anti-CD3 and IL-2, with or without VEGF for 14 days and the number of viable T cells was counted. Cytotoxic activity of cultured T cells and expression of VEGF receptor-2 (VEGFR-2), was assayed.Results:The addition of VEGF in cultures significantly reduced the number and proliferation rate of T cells in a dose-dependent manner and CD3 T cells expressed VEGFR-2 on their surface upon activation. Experiments with specific anti-VEGFR-2 antibodies revealed that the direct suppressive effect of VEGF on T-cell proliferation is mediated by VEGFR-2. We also showed that VEGF significantly reduced the cytotoxic activity of T cells.Conclusion:Our study showed that ascites-derived T cells secrete VEGF and express VEGFR-2 upon activation. Vascular endothelial growth factor directly suppresses T-cell activation via VEGFR-2. © 2012 Cancer Research UK.
Keywords: EGFR-2; immune suppression; Ovarian cancer; T cells; VEGF